Karakteristik Morfologi dan Indeks Ekologi Bulu Babi (Echinoidea) di Perairan Desa Wawama Kabupaten Pulau Morotai - Djainudin Alwi; Sandra Hi. Muhammad; Irwanto Tae (Jurnal Sumberdaya Akuatik Indopasifik, 2020)
Sea urchins are found in almost every area of ​​the islands which are scattered in Indonesia. One of them in Wawama Village, Morotai Island Regency. Local people use sea urchins as food, but the knowledge of sea urchins themselves is a food that has economic value. While the morphological and ecological aspects so far have not been known. This aims to study the morphological characteristics and analyze the ecological index of sea urchins. This research was conducted in November-December 2019 in the Village of Wawama, South Morotai District, Pulau Morotai District. The results showed that there were differences in the morphological characteristics of the types of sea urchins found in the study location both from body shape, color and external organs. The results of the ecological index analysis for the value of the density of sea urchins look varied, where the type of Diadema setosum has the highest value in all research stations. Species diversity at the three stations with a range of values ​​from 0.658 to 1.032-1.336 with an average value of 1.009, according to the species diversity criteria (H ') in the medium category Shannon Winner analysis. Evenness index (E) category is quite evenly distributed because the values ​​obtained ranged from 0.329 to 0.346 on average by 0.336 and the dominance index (C) was declared to be no species dominance because the values ​​obtained ranged from 0.275 to 0.535 with the mean of the three stations amounted to 0.396. Key words: Morphological characteristics; ecological index; sea ​​urchins